SEPSIS AND SEPTIC SHOCK: EPIDEMIOLOGY, CLINICAL PARAMETERS, AND PROGNOSTIC FACTORS IN A BRAZILIAN INTENSIVE CARE UNIT - Badin, Rebeka Caribé; Manaças, Liliane Rosa Alves; de Souza, Ivone Antônia (Arquivos de Ciências da Saúde da UNIPAR, 2023)
Sepsis is an organ dysfunction caused by a dysregulated host response to infection and is associated with high morbidity and mortality. The identification of prognostic markers in this syndrome has been a strategy to increase treatment efficacy. The objectives of this study were: 1) to describe the epidemiological and microbiological profile of septic patients and 2) to investigate the association between laboratory/clinical parameters and mortality rate, identifying prognostic markers. Using a prospective observational protocol, epidemiological, clinical and laboratory data were collected from adult patients with sepsis or septic shock admitted to a Brazilian Intensive Care Unit. During the study period, 120 patients were diagnosed with sepsis and 71.67% (n = 86) were included in the protocol. The overall mortality was 69.76% and chronic diseases were identified in 79.07% of cases. The mortality rates for sepsis and septic shock were 51.06% and 92.31%, respectively. SOFA scores on the first, third, and seventh days of hospitalization gradually increased for patients who had clinical worsening. Hyperlactatemia and hyperglycemia were identified in 45.9% and 27% of patients, respectively, and were associated with mortality. INR values greater than 1.5 or thrombocytopenia were related to 92.9% and 88.6% mortality, respectively. In the study, gender, age, ICU stay, site of infection and microbiological agent were not associated with the risk of death. However, the presence of comorbidities, high SOFA scores, three or more organ dysfunctions, and sepsis severity correlated directly with mortality rate.